ASPEK KETENTUAN PIDANA TERHADAP PELAKU TINDAK PIDANA KORUPSI KEPALA KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN TOBA DALAM PENERBITAN SERTIFIKAT HAK MILIK (Studi Putusan Nomor. 6/Pid.Sus-TPK/2023/PN.Mdn) - Yefta Nikoyas Tarigan; Alvi Syahrin; Edi Yunara (Journal Publicuho, 2025)
This study examines the criminal provisions applied to corruption cases involving the former Head of the National Land Agency (BPN) of Toba Regency in issuing a Land Ownership Certificate (SHM) No. 221. Corruption is categorised as an extraordinary crime due to its violation of social and economic rights. However, based on Articles 2 and 3 of Law No. 31 of 1999 on the Eradication of Corruption Crimes, as amended by Law No. 20 of 2001, the defendant was not proven to have committed any unlawful act, and no state financial loss was found. The judicial analysis also confirms that Ministerial Regulation No. 28 of 2015 and Ministerial Decree No. 1695 of 2022 only regulate sectoral technical criteria and do not classify the land as state property. The Supreme Court's cassation ruling on October 4, 2023, rejected the Public Prosecutor's appeal and upheld the acquittal. This study highlights the importance of precise legal interpretations in corruption cases to avoid judicial errors.